1994
DOI: 10.1212/wnl.44.4.721
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE)

Abstract: We studied the clinical, biochemical, and genetic features of eight patients with the autosomal recessive mitochondrial syndrome mitochondrial neurogastrointestinal encephalomyopathy (MNGIE). MNGIE is clinically characterized by ophthalmoparesis, peripheral neuropathy, leukoencephalopathy, gastrointestinal symptoms (recurrent nausea, vomiting, or diarrhea) with intestinal dysmotility, and histologically abnormal mitochondria in muscle. Brain MRI scans were consistent with leukodystrophy in seven patients exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
262
0
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(280 citation statements)
references
References 0 publications
8
262
0
9
Order By: Relevance
“…Although MNGIE is well recognized to cause severe gastrointestinal involvement,14, 15 our findings suggest that severe gastrointestinal involvement is much more common overall in m.3243A>G‐related mitochondrial disease. Thirteen percent of our patient cohort presented with severe gastrointestinal dysmotility symptoms with almost one third concomitantly presenting during an acute stroke‐like episode.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although MNGIE is well recognized to cause severe gastrointestinal involvement,14, 15 our findings suggest that severe gastrointestinal involvement is much more common overall in m.3243A>G‐related mitochondrial disease. Thirteen percent of our patient cohort presented with severe gastrointestinal dysmotility symptoms with almost one third concomitantly presenting during an acute stroke‐like episode.…”
Section: Discussionmentioning
confidence: 67%
“…Although gastrointestinal involvement, manifesting as intestinal pseudo‐obstruction (IPO), has been reported previously 9, 10, 11, 12, 13 and indeed is a recognized feature of the rare neurogastrointestinal encephalopathy (MNGIE) syndrome,14, 15 there remains a limited awareness of the severity of IPO in m.3243A>G‐related mitochondrial disease 16, 17…”
mentioning
confidence: 99%
“…These GI problems lead to extreme weight loss and reduced muscle mass (cachexia). 37,38 It is conceivable that similar functional defects could be involved in the Ant2 hypomorphic animals, and potential contribution of Ant2 mutations in clinical patients with gastroparesis should be a subject for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the mitochondrial proteins adenine nucleotide translocator 1 (ANT1) (Kaukonen et al), Twinkle (Spelbrink et al) and polymerase γ (Van Goethem et al) have been found to cause autosomal dominant progressive external ophthalmoplegia with multiple deletion of mtDNA. Mitochondrial Neurogastrointestinal Encephalomyopathy (MINGIE) is an autosomal recessive disorder due to loss-of-function mutations in the gene encoding thymidine phosphorylase, associated with multiple deletions, depletion and site-specific point mutations of mtDNA (Hirano et al, 1994;Nishigaki et al, 2003;Papadimitriou et al, 1998). ANT1 forms a homodimeric inner mitochondrial membrane channel that translocates ADP into ATP out of the mitochondrial matrix.…”
Section: Causes For Mtdna Depletion and Deletionmentioning
confidence: 99%